Sovereign Default, Domestic Banks, and Financial Institutions - GENNAIOLI, NICOLA; MARTIN, ALBERTO; ROSSI, STEFANO (Journal of Finance, 2014)
ABSTRACT We present a model of sovereign debt in which, contrary to conventional wisdom, government defaults are costly because they destroy the balance sheets of domestic banks. In our model, better financial institutions allow banks to be more leveraged, thereby making them more vulnerable to sovereign defaults. Our predictions: government defaults should lead to declines in private credit, and these declines should be larger in countries where financial institutions are more developed and banks hold more government bonds. In these same countries, government defaults should be less likely. Using a large panel of countries, we find evidence consistent with these predictions.